Active FXI Can Independently Predict Ischemic Stroke in Anticoagulated Atrial Fibrillation Patients: A Cohort Study - Ząbczyk, Michał Tomasz; Hanarz, Maksymilian; Malinowski, Krzysztof P.; Pociask, Elżbieta; Butenas, Saulius; Gajos, Grzegorz; Undas, Anetta (Thrombosis and Haemostasis, 2022)
Background Atrial fibrillation (AF) is associated with a prothrombotic state. Presence of active tissue factor (TF), activated factor IX (FIXa) and FXIa in circulating blood contributes to thrombosis. We investigated a prognostic value of these factors in AF patients.Methods In this cohort study, 284 AF patients (aged 63.3 ± 8.8 years) treated with oral anticoagulants were enrolled. Plasma levels of active coagulation factors were evaluated using thrombin generation assay. Concentrations of fibrinogen, D-dimer, interleukin-6 (IL-6), and endothelial damage markers, including von Willebrand factor (VWF) and soluble (s)E-selectin, were also measured. Ischemic stroke and cardiovascular death, analyzed separately or as a composite endpoint, were recorded during a mean follow-up of 47 months.Results Cerebrovascular events were observed in 20 patients (1.8%/year) who had at baseline higher fibrinogen, D-dimer, and VWF levels. Active TF and FXIa at enrollment were detectable in 12 (60%) and 15 (75%) patients who experienced ischemic stroke during follow-up. The composite endpoint observed in 23 patients (2.1%/year) was associated with increased concentrations of the above laboratory variables, along with 26% higher IL-6 levels. sE-selectin did not differ between the studied groups. On multivariable regression analysis, advanced age, anticoagulation discontinuation, and detectable FXIa, but not active TF, independently predicted the composite endpoint. No associations of FIXa with the study endpoints were observed.Conclusion FXIa present in circulating blood is associated with increased risk of ischemic stroke and cardiovascular death in anticoagulated AF patients during long-term follow-up. FXIa inhibition could be useful in cardiovascular prevention in AF beyond the current oral anticoagulation.
Keywords: anticoagulation; atrial fibrillation; factor XI; stroke; tissue factor